AI-enabled device digital forensics for smart cities - Kim, Sungbum; Jo, Wooyeon; Lee, Jino; Shon, Taeshik (Journal of Supercomputing, 2022)
Recently, smart cities provide various services to citizens through the convergence of Information and Communications Technology and industries such as transportation, health care, and automobiles. Accordingly, the number of smart devices that use artificial intelligence technology to store the personal information of users to provide services efficiently is increasing. Smart devices can be used to acquire key evidence through digital forensics, which can also serve, as evidence in a court. In this study, we acquire and analyze user data stored in wearable devices by applying a data acquisition framework for smart devices. This study contributes to the acquisition of key evidence for investigations.
Keywords: Artificial intelligence technologies; Information and communications technology; Personal information; Smart devices; User data; Wearable devices; Digital forensics; IoT; Smart city; Wearable device